Phylogenetic variability of human metapneumovirus strains circulating in Turkey during two consecutive epidemic seasons - Bayrakdar, Fatma; Altaş, Ayşe Başak; Korukluoğlu, Gülay (Mikrobiyoloji bülteni, 2016)
Human metapneumovirus (HMPV), classified in Paramyxoviridae family, phylogenetically consists of two major groups namely A and B, with genetic lineages of A1, A2 (comprises of sublineages A2a and A2b) and B1, B2. Although detailed evaluation on phylogenetic analysis of HMPV has been described in other countries, there are no data from Turkey on this subject. The aim of this study was to demonstrate for the first time, the phylogenetic diversity of HMPV strains circulating in Turkey during two consecutive epidemic seasons. A total of 2900 upper respiratory tract samples collected from patients with respiratory illness were evaluated between January 2011 and December 2013, without any special selection criteria. The presence of respiratory viruses in the samples were detected by real-time multiplex polymerase chain reaction (FTD® Respiratory Pathogens 21 Multiplex RT-PCR, Fast Track Diagnostics, Luxemburg), and 76 (2.6%) samples positive for HMPV were included in the study. HPMV nucleocapsid (N) (nt: 454-878) and fusion (F) (nt: 3624-4130) genes were selected for phylogenetic analysis. In sequence analysis, F and N gene sequences could only be obtained successfully from 46 out of 76 HMPV positive samples. According to sequences obtained, 54.3% belonged to B2, 17.4% to B1, 4.3% to A1, 4.3% to A2a, and 20% to A2b. In 2011, the A2b sublineage was predominant, while in 2012 and 2013, B2 lineages were predominant together with the B1 lineage. The A1 lineage was observed only in 2013. For the F gene fragment, nucleotide distance between group A and B was in the range of 0.138-0.168, however aminoacid distance amongst Turkish HMPV sequences were in the range of 0.028-0.042. For the N gene fragment, nucleotide distance between group A and B was in the range of 0.141-0.163, but aminoacid distance between group A and B was in the range of 0.037-0.050. Nucleotide diversity was higher than aminoacid diversity between and within lineages found in this study. This result indicated that the functional constraints on F and N genes prevent dramatic aminoacid changes, and indicated that the evolution of HMPV was slow. The seasonal peaks were observed from April to July in 2011, from January to June in 2012 and from January to May in 2013. In addition, our data emphasized that the HMPV prevalence was high in children 0-5 years old, and coinfections were common with the other respiratory viruses such as respiratory syncytial virus, coronavirus, parainfluenza virus 3, rhinovirus and enterovirus. In conclusion, this study showed that HMPV strains circulating in Turkey were similar to those circulating in Europe.